The Effect of Full Range Leadership and Safety Climate on Safety Performance is Mediated by Safety Motivation - Dewi Shanty; Bahtiar Usman; Yanki Hartijasti (Indonesian Journal of Business Analytics, 2025)
- This study aims to examine the extent to which safety motivation mediates the influence of full range leadership and safety climate on safety performance within the coal mining industry in Indonesia.A quantitative method was employed using cross-sectional and one-shot data techniques through a structured questionnaire distributed via Google Form. Data were processed using AMOS 23 and SPSS 26 software.Safety motivation fully mediates the influence of transformational, transactional, and laissez-faire leadership on safety performance. Safety motivation partially mediates the influence of safety climate on safety performance. Limitations and Recommendations – Future researchers may consider involving employees from other mining sectors such as nickel, sand, and gold or another industry. Respondents should also include individuals beyond staff-level positions. Originality/Value – This study investigates the influence of full range leadership and safety climate on safety performance, with safety motivation as a mediator. It presents a novel contribution by not merely replicating previous studies. Moreover, it incorporates both leadership style and safety climate in analyzing safety performance. The object of this study is the coal mining industry in Indonesia.